Factors Influencing on Human Resources Development in SMEs Service Enterprises in Industry 4.0: The Case of Thai Nguyen Province, Vietnam - Hanh, Phung Tran My (International Journal of Business, Economics and Management, 2020)
The study was conducted to analyze the factors and the level of influencing on human resource development for small and medium-sized service enterprises in Thai Nguyen province in Industry 4.0 because of artificial intelligence (AI) and the machines that make labor supply and labor fluctuations. With the dramatically changes of technology in the Industrial Revolution 4.0, jobs with creativity and flexibility, machines and robots cannot replace human resources. Employers will need high quality human resources, multi-disciplinary knowledge and flexible adaptations to changes in production methods in an era of technology. The research results show that there are 6 factors that positively influencing on human resource development for SMEs service enterprises in Thai Nguyen province in the Fourth Industrial Revolution.